Working memory updating training promotes plasticity & behavioural gains: A systematic review & meta-analysis. (November 2020) - Pappa, Katerina; Biswas, Viveka; Flegal, Kristin E.; Evans, Jonathan J.; Baylan, Satu
Highlights: WMU training produces neural modulation and large behavioural improvements in trained tasks in healthy adults. Near transfer effects are moderate, whilst there is no evidence of far transfer to general cognitive domains. The data suggest consistent fronto-parietal activity decreases, while the pattern for subcortical regions is less clear. There is a lack of studies assessing the effects of WMU training in neurological groups. Future neuroimaging studies should employ pretest-posttest active control group designs using multiple imaging modalities. Abstract: Aims: Recent reviews yield contradictory findings regarding the efficacy of working memory training and transfer to untrained tasks. We reviewed working memory updating (WMU) training studies and examined cognitive and neural outcomes on training and transfer tasks. Methods: Database searches for adult brain imaging studies of WMU training were conducted. Training-induced neural changes were assessed qualitatively, and meta-analyses were performed on behavioural training and transfer effects. Results: A large behavioural training effect was found for WMU training groups compared to control groups. There was a moderate near transfer effect on tasks in the same cognitive domain, and a non-significant effect for far transfer to other cognitive domains. Functional neuroimaging changes for WMU training tasks revealed consistent frontoparietal activity decreases while both decreases and increases were found for subcortical regions. Conclusions: WMU training promotes plasticity and has potential applications in optimizing interventions for neurological populations. Future research should focus on the mechanisms and factors underlying plasticity and generalisation of training gains.